Complementariedad de las láminas Rorschach y proyectivas: una demostración empírica - Jímenez Gómez, Fernando (1990)
This paper refers to the complementary contribution of Proyectives Cards to the Rorschach Inkblot Test, through the differents Categories and the principal factor of the Rorschach Test. A transversal study has been carried out on 526 adolescents and 300 adult Males and Females. We wish to point out that it is possible to appreciate, on the one hand, that Proyective Cards mean a complementary contribution to the Rorschach Test, and on the other, that adolescents show specific Rorschach protocols different to adults protocols. This study is complementary to the article published in the "Revista de Psicología" with the title: "Complementary contribution of Projectives cards to the Rorschach Psychodiagnostic Test".